EFL TEACHERS’ PERCEPTION TOWARD THE IMPLEMENTATION OF GENRE-BASED APPROACH IN INDONESIAN JUNIOR HIGH SCHOOLS - Kamil, Nursahid Nurul; Nafisah, Nia (Universitas PGRI Sumatera Barat, 2024)
This study aimed to investigate junior high school EFL teachers' perception toward the implementation of genre-based approach as a suggested teaching model of English from 2004 up to the newest curriculum. The design of this research was a descriptive qualitative study. It was clearly proved that teachers considered the GBA as an effective model that aligned with the current student-centered approach in the latest curriculum. Numerous teachers, unfortunately, confessed that they only utilized this model on exceptional cases since it demands students to have a wide range of cognitive skills as well as be passionately committed to learning. The data were collected through questionnaires and interviews with the 15 English teachers of junior high schools in Bandung, Indonesia. The findings showed that some teachers still needed help in implementing the stages of GBA, mostly at the stage of Independent Construction of the Text, due to a lack of teachers' training, resulting in many problems in the process of GBA implementation.